Diabetic ketoacidosis in a 9 month old child and the journey to 4 years - Chapp-Jumbo, Assumpta Udechi; Ijeoma, Stella (Acta Biomedica Atenei Parmensis, 2014)
We report a case of diabetes mellitus in a 9-month-old male, a product of a non-consanguinous marriage with no family history of diabetes mellitus. He presented initially with ketoacidosis in our emergency room and recovered from coma after 48 hours but was discharged after 14 days. He is now 4 years old and doing well and caregivers are coping even with the challenges of caring for a very young diabetic child. This article will help to build up the data bank for diabetes in infancy and childhood in our environment as well as highlight the challenges faced by both caregivers and physicians in the management of very young diabetics irrespective of socioeconomic status.